2006
DOI: 10.1007/s10961-006-7207-z
|View full text |Cite
|
Sign up to set email alerts
|

How Do Female and Male Faculty Members Construct Job Satisfaction? The Roles of Perceived Institutional Leadership and Mentoring and their Mediating Processes

Abstract: In this study we examine how a sample of 248 male and female professors at a Midwestern private research university construct their academic job satisfaction. Our findings indicate that both women and men perceive that their job satisfaction is influenced by the institutional leadership and mentoring they receive, but only as mediated by the two key academic processes of access to internal academic resources (including research-supportive workloads) and internal relational supports from a collegial and inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 24 publications
6
70
3
4
Order By: Relevance
“…Attention must also be paid to the social environment of departments. Bilimoria et al (2006) found that a "toxic" departmental climate had a stronger negative impact on women than on men, and that the quality of interactions with colleagues figured heavily in women's job satisfaction. Department chairs can play an important role in improving workplace climate, and several authors have advocated that chairs receive additional training to better address concerns within their departments (Hult et al 2005;Settles et al 2007) and to become more aware of the impact of implicit bias on the number and status of women in their department (Powell 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Attention must also be paid to the social environment of departments. Bilimoria et al (2006) found that a "toxic" departmental climate had a stronger negative impact on women than on men, and that the quality of interactions with colleagues figured heavily in women's job satisfaction. Department chairs can play an important role in improving workplace climate, and several authors have advocated that chairs receive additional training to better address concerns within their departments (Hult et al 2005;Settles et al 2007) and to become more aware of the impact of implicit bias on the number and status of women in their department (Powell 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many researches are conducted about the relationships between leadership and managerial styles and job satisfaction although there is no research done about the relationship between the SBL and other job variables except that of Coombe (2011). For instance, Beheshtifar and Nekoei-Moqadam (2010), Qolizadeh et al (2010), Bustankar (2010), Malekshahi et al (2010), Cesen (2009), Netherlands (2004, Bilimoria et al (2006), Elnaga (2012), and Thwala et al (2008) have unanimously stated that leadership, leadership style, managers' professional and fair behavior, their trustworthiness and support for employees are significantly related to job satisfaction. Ancona et al (as cited in Mohammadi, 2011) proved that innovative dimensions of the SBL have a considerable impact on job satisfaction, organizational commitment and organizational behavior of teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Considering issues related to the SBL along with the studies done in the area of the impact of leadership and management styles on job satisfaction (Cesen, 2009;Netherlands, 2004;Bilimoria et al, 2006;Thwala et al, 2008) and regarding the novelty of this concept in Iran, this research is conducted to recognize the status of SBL, leadership effectiveness and job satisfaction in addition to the way SBL affects leadership effectiveness and employees' job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The issue is that most of these do not further investigate implications for designing mentoring programs and do not reflect on the issues related to cross-or same-gender matching. For example, Bilimoria et al (2006) surveyed more than 248 professors from the same private US university, and show the relevance of mentoring for job satisfaction. They pinpoint to some gender differences: in the case of men, the relationship between job satisfaction and mentoring is mediated by both the academic resources available in their department and the internal support networks; for women, internal support networks are twice more important.…”
Section: The Mentee's Perspective and Mentoring Outcomesmentioning
confidence: 99%